PENINGKATAN PEMBELAJARAN KETERAMPILAN MULTIMEDIA CORELDRAW DI SMK YPUI PARUNG - Diki Rasapta; Octaviana Anugrah Ade Purnama (Abdi Jurnal Publikasi, 2023)
In the current era of globalization, technological advances are developing very rapidly and helping humans interact with each other without being limited by distance and time. The convenience provided by technology covers various aspects of life, from business to education. Technology plays an important role in helping every human need, one of which is the computer. The art of graphic design includes cognitive abilities and skills including typography, image processing, and page layout. The graphic designer arranges the appearance of the letters and the space of the composition to create an effective and communicative design. Graphic design covers all fields that require translating verbal language into visual design of text and images in various publication media in order to convey messages to communicants as effectively as possible. Coreldraw is an application that functions as a vector graphics editor that produces visual images. This application focuses on image editors, so it is widely used by users in the fields of advertising, visual design, printing, and other fields that require visualization formats. Some of the advantages of Coreldraw compared to other applications with the same function, include: 1) Ability to process lines and colors that are quite accurate; 2) Filled with various types of fonts to support creativity and imagination in processing brochures, pamphlets, book covers, and so on; 3) The level of clarity and detailed color specifications for the desired design; 4) Accuracy in designing, for example from the side of the line, line thickness, line curve, angle and line density.